Twin reversed arterial perfusion sequence in monochorionic diamniotic pregnancy: A rare occurrence (Indian Journal of Case Reports, 2024)
Twin reversed arterial perfusion is a rare complication occurring in monochorionic multifetal pregnancies. This condition is characterized by a malformed fetus being perfused by a normal twin through an artery-to-artery anastomosis in the reverse direction. Herein, we report a case of a multigravida female with a twin pregnancy at 27 weeks 5 days of gestation referred in view of twin pregnancy with the intra-uterine demise of one twin. Gray scale and color Doppler imaging revealed a monochorionic diamniotic pregnancy with a viable, normal twin, and an amorphously developed acardiac twin. The patient was monitored with weekly ultrasonography, echocardiography, and Doppler ultrasound examination to ascertain the well-being of the pump twin. She delivered a normal live baby at term and an acardius acephalus fetus. The perinatal mortality of the pump twin is significantly high. Therefore, it is necessary to diagnose this entity at an early gestational age through improved imaging techniques, so that timely intervention can be planned.